2009
DOI: 10.1161/hypertensionaha.108.118919
|View full text |Cite
|
Sign up to set email alerts
|

Vascular-Protective Effects of High-Density Lipoprotein Include the Downregulation of the Angiotensin II Type 1 Receptor

Abstract: Abstract-There is growing evidence that a cross-talk exists between the renin-angiotensin (Ang) system and lipoproteins.We investigated the role of high-density lipoprotein (HDL) on Ang II type 1 receptor (AT1R) regulation and subsequent Ang II-mediated signaling under diabetic conditions. To investigate the effect of HDL on AT1R expression in vivo, apolipoprotein A-I gene transfer was performed 5 days after streptozotocin injection. Six weeks after apolipoprotein A-I gene transfer, the 1.9-fold (Pϭ0.001) incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
61
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 39 publications
(36 reference statements)
2
61
0
2
Order By: Relevance
“…Uncoupling of eNOS is, besides NADPH oxidases (Cai 2005), an important source of reactive oxygen species in diseased, including diabetic, blood vessels (Hink et al 2001). Consistent with the demonstrated role of the angiotensin II receptor, type 1 (AT1R) in mediating increased NADPD oxidase activity, and eNOS uncoupling in diabetes (Oak and Cai 2007), the downregulation in diabetes-induced AT1R (Hodroj et al 2007;Nyby et al 2007) after apo A-I transfer (Van Linthout et al 2009) was postulated to be the predominant mediator of reduced NADPH oxidase activity and eNOS uncoupling. This hypothesis is further supported by in vitro findings showing that the HDL-mediated reduction in AT1R expression in human aortic endothelial cells was associated with a decline in hyperglycaemia-induced oxidative stress and a reduced responsiveness to angiotensin II (Van Linthout et al 2009).…”
Section: Human Apo A-i Gene Transfer Attenuates Diabetesassociated Oxmentioning
confidence: 75%
See 4 more Smart Citations
“…Uncoupling of eNOS is, besides NADPH oxidases (Cai 2005), an important source of reactive oxygen species in diseased, including diabetic, blood vessels (Hink et al 2001). Consistent with the demonstrated role of the angiotensin II receptor, type 1 (AT1R) in mediating increased NADPD oxidase activity, and eNOS uncoupling in diabetes (Oak and Cai 2007), the downregulation in diabetes-induced AT1R (Hodroj et al 2007;Nyby et al 2007) after apo A-I transfer (Van Linthout et al 2009) was postulated to be the predominant mediator of reduced NADPH oxidase activity and eNOS uncoupling. This hypothesis is further supported by in vitro findings showing that the HDL-mediated reduction in AT1R expression in human aortic endothelial cells was associated with a decline in hyperglycaemia-induced oxidative stress and a reduced responsiveness to angiotensin II (Van Linthout et al 2009).…”
Section: Human Apo A-i Gene Transfer Attenuates Diabetesassociated Oxmentioning
confidence: 75%
“…Consistent with the demonstrated role of the angiotensin II receptor, type 1 (AT1R) in mediating increased NADPD oxidase activity, and eNOS uncoupling in diabetes (Oak and Cai 2007), the downregulation in diabetes-induced AT1R (Hodroj et al 2007;Nyby et al 2007) after apo A-I transfer (Van Linthout et al 2009) was postulated to be the predominant mediator of reduced NADPH oxidase activity and eNOS uncoupling. This hypothesis is further supported by in vitro findings showing that the HDL-mediated reduction in AT1R expression in human aortic endothelial cells was associated with a decline in hyperglycaemia-induced oxidative stress and a reduced responsiveness to angiotensin II (Van Linthout et al 2009). These observations underline the finding of Tolle et al (2008), who showed that HDL reduce NADPH oxidase-dependent reactive oxygen species generation via inhibition of the activation of Rac1, which is a downstream AT1R-dependent mediator of angiotensin II (Ohtsu et al 2006).…”
Section: Human Apo A-i Gene Transfer Attenuates Diabetesassociated Oxmentioning
confidence: 78%
See 3 more Smart Citations